On the analytical solution for the slewing flexible beam-like system: Analysis of the linear part of the perturbed problem - Fenili, Andre; Balthazar, Jose Manoel [UNESP] (Polish Soc Theoretical & Applied Mechanics, 2008)
The dynamical system investigated in this work is a nonlinear flexible beam-like structure in slewing motion. Non-dimensional and perturbed governing equations of motion are presented. The analytical solution for the linear part of these perturbed equations for ideal and for non-ideal cases are obtained. This solution is necessary for the investigation of the complete weak nonlinear problem where all nonlinearities are small perturbations around a linear known solution. This investigation shall help the analyst in the modelling of dynamical systems with structure-actuator interactions.
Keywords: non-ideal system; flexible structure; perturbed equations; analytical solution